Pulmonary vascular anomalies: a review of clinical and radiological findings of cases presenting with different complaints in childhood - Nacaroğlu, Hikmet Tekin; Ünsal-Karkıner, Canan Şule; Bahçeci-Erdem, Semiha; Özdemir, Rahmi; Karkıner, Aytaç; Alper, Hüdaver; Can, Demet (The Turkish Journal of Pediatrics, 2016)
Congenital pulmonary vascular abnormalities arise from several etiologies. These anomalies are difficult to categorize and sorted into distinct classifications. Major pulmonary vascular abnormalities can be ranked as interruption of the main pulmonary artery or its absence, emergence of the left pulmonary artery in the right pulmonary artery, pulmonary venous drainage abnormalities, and pulmonary arteriovenous malformations (PAVMs). Some of the cases are asymptomatic and diagnosed by coincidence, whereas a few of them are diagnosed by typical findings in the newborn and infancy period, symptoms, and radiological appearances. Early diagnosis is important, since death may occur as a result of pulmonary and cardiac pathologies developed in patients with pulmonary vascular anomalies. In this case presentation, the clinical and radiological findings of patients that presented with different complaints and were diagnosed with pulmonary vascular anomalies were introduced.